PENGARUH PENERBITAN SUKUK TERHADAP REAKSI PASAR MODAL SYARIAH (Studi Empiris di BEI tahun 2018) - Ahmad Syarifudin; Afifudin Afifudin; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACT The development of a good capital market in a country is one of the characteristics of an advanced industrial country, because the capital market is one of the important elements to measure the economic progress of a country. Information on bond issuance for investors is good information, because investors judge that bond issuance shows companies are able to improve company performance. This information can have an impact on stock prices if the information gets a positive response from investors. The researcher conducted this study aimed to determine the effect of sukuk issuance on the reaction of the Islamic capital market. This study included quantitative research with a sample of 23 sukuk issuance and using secondary data which included financial statements, Jakarta Islamic index, sukuk rating, sukuk issuance value. Data analysis using data normality test, classic assumption test, multiple linear regression analysis, and hypothesis testing. The analysis found that the value and rating of sukuk issuance simultaneously had a significant effect on the reaction of the Islamic capital market, to partially analyze the value and rating of sukuk issuance significantly influenced the reaction of the Islamic capital market.  Keywords: Sukuk Value, Sukuk Rating, and Islamic Capital Market